LOOKING INTO AN APPROPRIATE METHODOLOGY FOR THE EMBANKMENT DESIGN AND CONSTRUCTION ON SOFT SOILS - S. Oztoprak; S. F. Cinicioglu (International Association of Lowland Technology, 2007)
The difficulty of simulating real field behavior during design stage causes construction difficulties that could not be foreseen for the embankments on soft clays. Although observational method seems to be the only tool to overcome these problems, the conventional observational methods suffer from the time lags between parameter revision and next stage of construction. New methodologies are needed which provide direct links between measurements and adjustment of parameters. The Oztoprak & Cinicioglu method is a modern version of the observational method for embankments on soft clays. In this paper, the applications and outcomes of this method on the two embankments; Cubzac-les-Ponts and Stanstead Abbotts, were outlined and compared with the findings by the application of two FE softwares; the Sage Crisp and Plaxis. These comparisons should be interpreted as the comparison of real behavior and highly effective prediction tools. The results indicated the incomparable effectiveness of the field measurements based approach but this does not imply that prediction methods should be overlooked, instead their capacities should be enhanced by the information gained through real nature of field behavior.